The complex interactions of Ostreid herpesvirus 1, Vibrio bacteria, environment and host factors in mass mortality outbreaks of Crassostrea gigas. (23rd August 2018) - Alfaro, Andrea C.; Nguyen, Thao V.; Merien, Fabrice
Abstract: From the first detection in the Eastern oysters ( Crassostrea virginica ) in 1972, herpes‐like viruses/herpesviruses have been identified in at least 20 bivalve species and have caused massive mortalities in six cultured species of bivalves. Among them, the Pacific oyster ( Crassostrea gigas ) is most threatened by massive mortalities associated with detection of Ostreid herpesvirus 1 (OsHV‐1) and its variants. These mortality events have been reported in more than 12 countries, and OsHV‐1 itself has been reported in 15 countries worldwide. Traditionally, the genotype OsHV‐1 (or OsHV‐1 Var) is the main contributor to bivalve mortalities, but the emergence of variants (e.g. OsHV‐1 μVar and related ones, acute viral necrosis virus—AVNV, OsHV‐1‐SB) is now responsible for new mortality outbreaks in Pacific oysters and other bivalve species. In addition to OsHV‐1, Vibrio bacteria and other abiotic and host factors also significantly contribute to mortality outbreaks. To this end, the current contribution aims to synthesize the body of literature on our current knowledge of these mass mortality events to provide insights into the role of each risk factor and complex interactions in the disease process. Specifically, this review encompasses our current knowledge and critical gaps. Important suggestions for future investigation are also presented.